2006
DOI: 10.1093/rheumatology/kei240
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tobacco smoking and rheumatoid factor seropositivity on disease activity and joint damage in early rheumatoid arthritis

Abstract: Tobacco smoking has an adverse effect on patients with early RA and this is possibly immunologically mediated. IgM RF does not predict poorer prognosis in RA unless it is associated with a concomitant elevation of IgA RF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
64
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 34 publications
12
64
0
3
Order By: Relevance
“…Smokers are more likely to have citrullinated proteins in lung lavage [19], and they have increased rheumatoid arthritis disease activity [20]. As reported by other investigators, in our cohort, smoking was associated with a UIP pattern on HRCT.…”
Section: Discussionsupporting
confidence: 79%
“…Smokers are more likely to have citrullinated proteins in lung lavage [19], and they have increased rheumatoid arthritis disease activity [20]. As reported by other investigators, in our cohort, smoking was associated with a UIP pattern on HRCT.…”
Section: Discussionsupporting
confidence: 79%
“…A combination of genetic predisposition, immunological deregulation and environmental factors contribute to its pathogenesis [1]. The most recognized environmental risk factor for the development and severity of RA is cigarette smoking [2][3][4]. RA synovium is characterized by synovial hyperplasia and infiltration of inflammatory cells together with high production of proinflammatory cytokines such as tumor necrosis alpha (TNFα) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Manfredsdottir et al 44 found gradient of increase in disease activity was observed from never smokers to former smokers to current smokers defined by number of swollen joints (SJC), tender joints (TJC) and visual analogue scale for pain, while Vesperini V et al 45 foundsmoking status had no significant effect on disease activity and disability but did reduce 1-year radiographic disease progression, this due to difference in number of smoker and non smoker in that study the number of smoker was 138 and 335 was non smoker while in our study the number of smoker was 22 while non smoker was 78.…”
Section: Discussionmentioning
confidence: 99%